Pengaruh Proses Rekrutmen, Seleksi Dan Gaji Terhadap Kinerja Karyawan Pada Bank Syariah Indonesia Kcp. Panyabungan: Sahnan Batubara - Sahnan Batubara (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2026)
AbstractThe purpose of this study is to examine the importance of human resourcem anagement in improving employee performance in the Islamic banking sector, particularly in the context of effective recruitment and selection, as wellas a fair pay system. The objective of this study was to analyze the influence of recruitment, selection, and salary processes on employee performance at BSI Panyabungan Branch Office. The research method used was aquantitative approach, with questionnaires distributed to 14 employees. The results of the study indicate that: (1) The recruitment process has a significant effect on BSI Panyabungan employee performance with a significance value of 0.000 < 0.05 and tcount > ttable with a value of 5.485 > 1.782 (2) Employee selection does not have a significant effect with a significance value of 0.610; (3) Salary does not have a significant effect with a significance value of 0.916; and (4) Simultaneously, recruitment, selection and salary have a significant effect on employee performance, with a calculated Fvalue > Ftable with a value of 16.954 > 3.587 and a significance of 0.000 < 0.05. Keywords: Recruitment, Selection, Salary, Employee Performance, Islamic Bank